Perceptions of Cardiovascular Healthcare Professionals Regarding Clinical Trials: A Survey-Based Study from the Middle East - Zainab Atiyah Dakhil; Hasan Ali Farhan; Mohammed Dheyaa Marsool; Mohammed Saad Qasim; Michele Peters; Jose Leal (Global Heart)
Background: Low-middle income countries harbor the highest burden of cardiovascular diseases globally, but there is an under-representation of these countries in cardiovascular clinical trials. This limits the generalizability of the trial results to these countries. There is a lack of data on insights of cardiologists in these countries regarding conducting and participating in clinical trials. We sought the views of cardiovascular healthcare professionals in Iraq on participation in clinical trials. Method: Cardiovascular professionals in Iraq were identified and contacted, via special platforms on social media specified for them, to answer a 30-item online survey. Results: We surveyed n = 255 specialists (20% were women); interventional cardiologists constituted 44.7%, followed by cardiology trainees at 31%. Almost 30% reported having been involved in clinical trials, with data collection being the more frequently reported role (21.2%). Prior participation was not significantly associated with respondent gender, academic affiliation, or presence of institutional ethical committee. Of the total, 95.7% thought that clinical trials should be conducted in Iraq, with 58.8% reporting that they would participate if invited. The most common barriers to respondents’ participation in trials were lack of electronic health records (52.2% of those surveyed) and time (51.4%), followed by the requirement of additional follow-up visits or investigations (34.1%). The most common motivators were establishing electronic health records (86.27%), education and training of the general population about clinical trials (84.7%), and dedicated training for healthcare providers about clinical trial basics (84.3%). Conclusion: Our work helps pave the path to implementing a robust clinical trial ecosystem in Iraq. Institutional and financial factors and a lack of dedicated research time are related to the cardiovascular clinical trial lag in Iraq. Future qualitative research can help in getting a deeper understanding of what is needed to create the right infrastructure.